New Public Management (NPM) as an Effort in Governance - Charity Latanza Indahsari; Sam'un Jaja Raharja (Jurnal Manajemen Pelayanan Publik, 2020)
New Public Management (NPM) is an approach in public administration that applies knowledge and experience gained in the world of management and other disciplines to improve the efficiency and effectiveness of public service performance in modern bureaucracies. New public management focuses on public sector management that is performance-oriented, not policy-oriented. Based on the results of this study, there were three policies or strategies in the New Public Management (NPM) as an effort in governance, which were the reorganization of public administration, decentralization of partnerships and networks, and innovation. The purpose of making this literature review was to add insight into the New Public Management (NPM) as an effort in governance. The method used in this research was Study Literature Review (SLR), using several articles found in searches on Scopus, which were published in the last five years.